A Content Analysis of the TikTok Account @amiirahanugrah: The Representation of Halal Food at 7-Eleven Stores in Thailand - Mochammad Abdul Machfud; Asidigisianti Surya Patria; Abdul Hafidz; Nova Kristiana; Arieviana Ayu Laksmi; Yunia Dwie Nurcahyanie; David Nugroho (Sean Institute, 2025)
The rise of TikTok is particularly relevant in the food industry, where engaging visual content communicates product appeal. This study analyzes how halal food is represented in the TikTok account @amiirahanugrah, specifically regarding 7-Eleven Thailand products. The purpose is to identify the main themes and strategies used in presenting halal food. Using qualitative content analysis on three selected videos, the study reveals that the creator effectively acts as a